379 Frequency and molecular associations of KRAS mutations in gynecologic malignancies. (13th November 2020) - Kilowski, K; Dietrich, M; Xiu, J; Ahmad, S; Manyam, M; Fitzsimmons, C; Kennard, J; McKenzie, N; Kendrick, J; Korn, M; Holloway, R
Abstract : Introduction: KRAS inhibitors have efficacy with non-small cell lung, pancreatic, and colon cancers. The therapeutic role in gynecologic malignancies remains investigational. Methods: Caris next-generation sequencing profiles of 859 gynecologic cancers from our institution were queried for KRAS- and BRCA-mutations, microsatellite instability (MSI), and tumor mutational burden (TMB). Wilcoxon and Fisher-Exact tests were used for comparison of molecular signatures and p<0.05 was regarded significant. Results: KRAS-mutations were present in 12.7% (33/259) uterine [endometrial cancer (EC)] and 6.7% (27/404) ovarian cancers (OC). KRAS-mutations in Type I vs. Type II EC were 20.7% (19/92) and 9.4% (13/139), respectively, and 3.6% (1/28) sarcoma. KRAS-mt OC by histologies were: papillary serous (9/306, 2.9%), endometrioid (9/23, 39.1%), mucinous (4/5, 80%), MMMT (3/38, 7.9%), clear cell (2/17, 11.8%), granulosa (0/10, 0%), and other histology (0/5, 0%) (table 1 ). KRAS-mutations were limited to exon 2. (for subtypes, see figures 1A and 1B). BRCA1/2-mt and KRAS-mutations were mutually exclusive in both EC and OC. KRAS-mutated EC had a greater association with MSI-H (34.8% KRAS-mt vs 16.4% KRAS-wt, p=0.0445) and TMB (median=9 mt/MB vs 8 mt/MB, p=0.0123) than KRAS-wt. No difference in TMB and MSI status was seen between KRAS-mt vs KRAS-wt OC. Conclusions: KRAS mutations in exon 2 are frequent in uterine and ovarian malignancies. Clinical trials evaluating subtype-specific KRAS inhibitors in uterine and ovarian tumors are warranted.